Medical Caregiving Narratives of the First World War - Allitt, Marie (Edinburgh University Press, 2023)
This book offers a novel critical intervention in medical humanities, foregrounding the importance of spaces and senses in medical experiences. It explores the distinctive experience and literary representations of somatic and sensuous geographies in First World War medical caregiving life writing. It demonstrates the complex situation of the medic, who is vulnerable both vicariously and directly to the effects of physical and psychological harm. Chapters look at the medic’s relationship with the war environment; the spaces in which medical care takes place; bodies and the wounds of patients in medical narratives; and psychological and imaginative landscapes and textual spaces where complex emotions, trauma, coping and survival are examined.